Outward investment of Portuguese small and medium enterprises in the Central and Eastern European countries: motivations and challenges - Santos, Eleonora (2022)
Background: This paper identifies the determinant factors of Portuguese investment in Poland, Hungary, and the Czech Republic. We assume that investment abroad is motivated by business opportunities, and the quality-price ratio of the workforce. Methods: To this end, we used a qualitative methodology composed of 6 case studies, based on interviews and surveys with the managers of the Portuguese firms investing in those three economies. Results: Despite the business opportunities, Portuguese investment directed towards these economies is negligible, due, in part, to the geographic and cultural distance. However, the economic and political stability, combined with market size and growth potential are undeniable attraction factors for Portuguese investors. Small and medium enterprises (SMEs), due to their flexible conditions that allow changes in the activity, and the strong trend towards outsourcing, to the detriment of the manufacturing industry, are the primary focus of international investment. This trend, although common to several sectors, has shown greater dynamism in the banking and financial sector. Conclusions: The results suggest market-oriented investments aiming at growth and expansion. The vast Polish market is the one that most attracted Portuguese investors. The hybrid feature of some strategies can align with the cautious attitude towards the investment translated into cooperation agreements with financial institutions for funding, the market learning process, and the training of the personnel. The anticipation of the installation over potential competitors, the experience in production and international markets, the price-quality ratio, the capacity of product adaptation and the design were considered important sources of competitive advantage that motivated the investment. The greatest difficulties during this process were language and the complexity of legislation.